GURU DAN MURID DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Sumiati, Sumiati; Barni, Mahyuddin (STIT Ibnu Rusyd Tanah Grogot, 2023)
This article aims to find out how the concept of teacher and student is according to the Qur'an and Hadith. The framework used to analyze this theme is a thematic study based on the discussion on the arguments of the Qur'an and Hadith in understanding the meaning of words and the essence of the concept of the teacher and student itself. The discussion that will be raised is the understanding of teachers and students from the perspective of the Qur’an and hadith. Because education is an activity that involves at least 2 individuals who are interrelated and interact with each other, which we know as teacher and student. Teachers are all those who try to improve others Islamically. They can be parents (fathers and mothers), uncles, siblings, neighbours, religious leaders, community leaders, and the wider community. As for students, they are people who want to get knowledge, experience and a good personality to equip their lives so they can be happy in this world and the hereafter by studying earnestly.